2002
DOI: 10.1002/cncr.10661
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of induction chemotherapy with paclitaxel, ifosfamide, and carboplatin (TIC) for patients with locally advanced squamous cell carcinoma of the head and neck

Abstract: BACKGROUND. This Phase II trial was conducted to determine the response rate,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 35 publications
3
24
0
1
Order By: Relevance
“…Similar to our results, Shin et al [25] reported a complete remission rate of 31% and a partial remission rate of 50%, with a local control rate of 81% and an overall survival at 1 and 2 years of 88 and 82%, respectively. Klug et al [26], representing 222 patients, reported an overall survival of 55% after 5 years and a local control probability of 74%.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar to our results, Shin et al [25] reported a complete remission rate of 31% and a partial remission rate of 50%, with a local control rate of 81% and an overall survival at 1 and 2 years of 88 and 82%, respectively. Klug et al [26], representing 222 patients, reported an overall survival of 55% after 5 years and a local control probability of 74%.…”
Section: Discussionsupporting
confidence: 81%
“…Its effectiveness concerning locoregional tumor control and recurrence-free survival was shown [6] previously, as well as a good activity of the combination with paclitaxel/carboplatin [11,21,22,23,24]. This high effectiveness was confirmed by the initially published 1- and 3-year results of the presented study where the overall survival rate after 3 years was 84% [25]. At the same time, low toxicity, mainly mucositis but also dermatitis, thrombopenia and leukopenia could be managed with adequate supportive treatment.…”
Section: Discussionsupporting
confidence: 76%
“…Thirty-five deaths occurred, 18 of which were from disease progression, six were treatment-related, two were from a second primary, and nine were from other medical causes, Argiris, Haraf, Kies et al 352 including toxicity. Although the induction chemotherapy with PFL-interferon was associated with considerable toxicity, its activity was comparable with newer taxane-based combination regimens, such as carboplatin, ifosfamide, and paclitaxel (TIC), cisplatin, 5-FU, leucovorin, and docetaxel (TPFL), and cisplatin, 5-FU, and docetaxel (TPF), that are currently under evaluation [36][37][38]. The reported survival rates with FHX were very promising, but locoregional control remained a major challenge.…”
Section: Induction Chemotherapy Followed By Fhxmentioning
confidence: 99%
“…A more aggressive, multiday regimen that added ifosfamide (TIC) has also been reported with considerable success in a phase II trial, but additional toxicity and a complicated therapy may outweigh marginally different response rates afforded by the addition of ifosfamide [11]. The use of carboplatin with paclitaxel takes advantage of the lower neurotoxicity of carboplatin compared with cisplatin and permits high-dose combinations and even weekly combination treatments with paclitaxel, which is neurotoxic.…”
Section: Introductionmentioning
confidence: 99%